2019
DOI: 10.1088/1748-9326/ab2c7e
|View full text |Cite
|
Sign up to set email alerts
|

European warm-season temperature and hydroclimate since 850 CE

Abstract: The long-term relationship between temperature and hydroclimate has remained uncertain due to the short length of instrumental measurements and inconsistent results from climate model simulations. This lack of understanding is particularly critical with regard to projected drought and flood risks. Here we assess warm-season co-variability patterns between temperature and hydroclimate over Europe back to 850 CE using instrumental measurements, tree-ring based reconstructions, and climate model simulations. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 112 publications
5
75
0
1
Order By: Relevance
“…This may demonstrate that dynamic atmospheric processes are present in generating cyclone-related precipitation extremes throughout the LIA (Raible et al 2018), departing from the Clausius-Clapeyron thermodynamic expectations of an increase in precipitation intensity associated with atmospheric warming (Pall et al 2007, Trenberth 2011, Trenberth et al 2014, Kirby 2016, Prein and Pendergrass 2019. Our study thus shows the same tendency as revealed by Ljungqvist et al (2019) for a negative low-frequency temperature-hydroclimatic coupling (i.e., warm and dry) in southern Europe. Likewise, solar-type periodicities suggest that the Sun may be one of the precursors of hydrological processes in northern Italy (Zanchettin et al 2008).…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…This may demonstrate that dynamic atmospheric processes are present in generating cyclone-related precipitation extremes throughout the LIA (Raible et al 2018), departing from the Clausius-Clapeyron thermodynamic expectations of an increase in precipitation intensity associated with atmospheric warming (Pall et al 2007, Trenberth 2011, Trenberth et al 2014, Kirby 2016, Prein and Pendergrass 2019. Our study thus shows the same tendency as revealed by Ljungqvist et al (2019) for a negative low-frequency temperature-hydroclimatic coupling (i.e., warm and dry) in southern Europe. Likewise, solar-type periodicities suggest that the Sun may be one of the precursors of hydrological processes in northern Italy (Zanchettin et al 2008).…”
Section: Resultssupporting
confidence: 47%
“…This is distinctly visible in figure 4(a), which shows that ASSIS(GF) is only little accentuated in this drier period in the ninth and tenth centuries. Between c. 750 and 1250 CE, southern Europe, including northern Italy, tended to receive relatively low amounts of precipitation, at least in summer, whereas the temperature, on average, was higher (Luterbacher et al 2016, Ljungqvist et al 2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Europe also spans steep climate gradients, such that we can study the targeted possible emergent large-scale patterns of soil moisture co-variation with other hydro-climatic variables in and across the three main European climate regions distinguished and proposed by the Intergovernmental Panel on Climate Change (IPCC) as appropriate for managing risks of extreme events and advancing climate change adaptation 2 : Northern Europe (NEU), Central Europe (CEU), and Southern Europe (SEU). Recent large-scale multi-catchment studies of current 5 and past 26 hydro-climate across Europe have also shown distinctly different large-scale characteristics of these three climate zones with regard to soil moisture anomaly responses to atmospheric driver variations. To also assess data uncertainty effects, the analysis combines the three alternative data products into a fully independent set for a basic study, as well as an internally consistent and an intermediate dataset for comparative study (Table 1).…”
mentioning
confidence: 99%
“…Terms used in the CMEI to describe the meteorological events and the assigned indices (i t = temperature index; i r = precipitation index). It is interesting to consider the combined effect of the thermal and pluviometric (rainfall) regimes [22,23]. To do this, the differences between the percentages of wet and dry (warm and cold) weather records were calculated for each year and represented, as shown, in Figure 3d.…”
Section: Of 18mentioning
confidence: 99%